3D-printed guides versus computer navigation for pedicle screw placement in the surgical treatment of congenital scoliosis deformities - Hui-Fa Xu; Chao Li; Guoliang Tang; Tian-Qing Li; Zong-Zhi Fan; Lu-Yu Huang (Journal of Orthopaedic Surgery, 2024)
Background To compare the safety and clinical outcomes of 3D-printed guides versus computer navigation for pedicle screw placement in the correction of congenital scoliosis deformities. Methods The study was a single-centre retrospective controlled study and was approved by the hospital ethics committee for the analysis all patients under the age of 18 years with at least 2 years of follow-up. Sixty-three patients who underwent surgical correction for congenital scoliosis deformities in our hospital from January 2015 to December 2020 were divided into two groups based on the decision following preoperative doctor‒patient communication. Among them, 43 patients had pedicle screws placed with 3D-printed guider plates, while the remaining 20 patients had screws inserted with the assistance of computer navigation. The perioperative period, follow-up results and imaging data were compared between the groups. Results The operation was completed successfully for patients in both groups. The 3D-printed guide-assisted screw placement technique proved to be significantly superior to the computer navigation technique in terms of operation time, screw placement time, and intraoperative blood loss ( p < .05), although the former had more frequent intraoperative fluoroscopies than the latter ( p < .05). The mean follow-up time was 41.4 months, and the SRS-22 scores significantly improved in both groups over time postoperatively ( p < .05). The 3D-printing group had better SRS-22 scores than the navigation group 6 months after surgery and at the last follow-up ( p < .05). Compared with preoperative values, the coronal Cobb angle, local kyphotic Cobb angle, C7-S1 coronal deviation (C7PL-CSVL), and sagittal deviation (SVA) were significantly improved in both groups after surgery ( p < .05). Conclusion Both techniques achieve the purpose of precise screw placement and proper correction of the deformities. In contrast, the 3D-printed guide-assisted screw placement technique showed advantages in terms of operation time, screw placement time, intraoperative blood loss and patient satisfaction with outcomes.